Analisis Efektivitas Sistem Informasi Absensi Berbasis Fingerprint dalam Meningkatkan Disiplin Kerja - Adam Saputra; Remo Yudianto; Zibran Briliantama (Journal of Information Systems and Business Technology, 2025)
Using information systems in companies is becoming more important to help with managing daily operations and keeping employees disciplined. One common technology used is the fingerprint-based attendance system, which is believed to reduce fake attendance and help employees be on time. This study looks at how effective the fingerprint attendance system is in helping with work discipline. The study used a quantitative approach, collecting data through observation, surveys, and documents. The people involved were employees who used the fingerprint system every day. The results show that the system helps make attendance more accurate, improves punctuality, and ensures employees follow their scheduled working hours. It also helps managers track attendance more easily and gives them reliable data for making decisions. However, some problems were found, mainly due to technical issues and reliance on good infrastructure. Overall, the fingerprint-based attendance system is effective in improving work discipline, but it needs ongoing checks and improvements to keep working well.